The Use of Quizziz Platform to Improve Students' Mastery of English Vocabulary - Tiara putri salsabila adiyanto; Lusia Alvika Florence Susar; Zinedine Zidane; Cici Situmorang (Journal of Innovative and Creativity, 2026)
This study aims to explore the use of the Quizizz platform in improving students' English vocabulary mastery. This study uses a descriptive qualitative method that focuses on students' perceptions, learning experiences, and motivation in utilizing Quizizz as a learning medium. The research participants consisted of seventeen students from the English Education Study Program at IPB Cirebon who were selected through purposive sampling based on their experience in using Quizizz. Data collection was conducted through semi-structured interviews, questionnaires, and classroom observations. The data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results showed that the use of Quizizz had a positive impact on students' English vocabulary mastery by increasing their learning motivation, active involvement, and participation in learning. The gamification feature and instant feedback helped students memorize vocabulary more effectively and created a pleasant learning atmosphere. Thus, it can be concluded that Quizizz is an effective and relevant supporting medium for improving English vocabulary learning in higher education.